Recovery or Illusion? Assessing Corporate Performance and Investor Views in the Aftermath of Crisis - Resi Ariyasa Qadri; Maureen Novita Jawak (Journal of Applied Accounting and Taxation, 2024)
This research is dedicated to examining the pre-and-post impact of the COVID-19 pandemic on the financial outcomes and market perceptions within the consumer goods industry, specifically focusing on the food and beverage segment. Employing a purposive sampling strategy for data collection and difference testing methods for analysis, this study adopts a quantitative approach to fulfill its objectives. The analysis incorporated a final sample comprising 15 companies within the food and beverage sector. Market perception was assessed using Tobin's Q ratio, while financial performance was evaluated through five distinct ratios. These ratios were subjected to an exhaustive examination utilizing both parametric and non-parametric difference tests. The empirical results reveal that, except for the debt ratio, which remained statistically unchanged, the other four ratios"”current ratio, total assets turnover ratio, return on investment ratio, and earnings per share ratio"”exhibited significant alterations pre-and-post-pandemic. Market valuation remained consistent across the temporal divide. This investigation contributes valuable insights into the financial health and market perceptions of companies, offering investors a refined basis for making informed decisions. Furthermore, this study underscores the applicability of signaling theory within the realm of accounting research.